Acupuncture for Adult Obstructive Sleep Apnea or Obstructive Sleep Apnea-Hypopnea Syndrome: A Review of the China National Knowledge Infrastructure Database - Hye Kyung Baek; Young Jun Kim; Yeon Sun Lee; Hye Ri Jo; Mi So Park; Dong Guk Shin; Hyun A Shim (MEDrang Inc., 2022)
The purpose of this study was to analyze acupuncture treatment methods and acupoints used to treat obstructive sleep apnea (OSA) or obstructive sleep apnea-hypoapnea syndrome (OSAHS). The data were retrieved from January 2010 to May 2022 from the China National Knowledge Infrastructure database. The search terms included "adult," "obstructive sleep apnea," "obstructive sleep apnea hypoapnea syndrome," "acupuncture," and "electro-acupuncture." Clinical trials for acupuncture treatment of OSA or OSAHS were included in this review (4 non-randomized controlled studies, 1 was a case report, and 10 randomized controlled studies). For OSA and OSAHS treatment, the acupoints that were most frequently used included REN23, LU7, ST40, EX9, LI11, and DU20. Compared with the control or Western treatment group, the treatment outcome measures of participants in the acupuncture treatment group significantly improved. In some studies, participants in the acupuncture group did not have side effects and the treatment was cost-effective. The data analyzed in this review suggest that acupuncture is an effective treatment for OSA or OSAHS.